The photon PDF from high-mass Drell-Yan data at the LHC - Giuli, Francesco; Lisovyi, Mykhailo (The European physical journal. C, Particles and fields, 2017)
Achieving the highest precision for theoretical predictions at the LHC requires the calculation of hard-scattering cross sections that include perturbative QCD corrections up to (N)NNLO and electroweak (EW) corrections up to NLO. Parton distribution functions (PDFs) need to be provided with matching accuracy, which in the case of QED effects involves introducing the photon parton distribution of the proton, xγ(x,Q2)xγ(x,Q2)xγ (x,Q^2). In this work a determination of the photon PDF from fits to recent ATLAS measurements of high-mass Drell-Yan dilepton production at s√=8s=8\sqrt{s}=8 TeV is presented. This analysis is based on the xFitter framework, and has required improvements both in the APFEL program, to account for NLO QED effects, and in the aMCfast interface to account for the photon-initiated contributions in the EW calculations within MadGraph5_aMCNLO. The results are compared with other recent QED fits and determinations of the photon PDF, consistent results are found.
First online: 15 June 2017
Gesehen am 02.07.2018